10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ObjectiveTo investigate the interfering factors and correction methods in the determination of serum uric acid (UA) using the uricase method in patients with elevated immunoglobulin M (IgM).Materials and MethodsIn clinical practice, the UA levels of five patients with elevated IgM were measured using the Beckman AU5800 analyzer with its reagents or Zhongyuan reagents. The reaction curves were analyzed. Three methods dilution with normal saline, dilution with saturated saline, and polyethylene glycol 6000 (PEG 6000) precipitation were applied to eliminate interference. For comparison, UA was also measured using the Abbott Ci8200 analyzer with its reagents.ResultsThe serum IgM levels for cases 1 to 5 were 12.39, 27.0, 12.09, 7.33, and 11.05 g/L, respectively. The initial UA results obtained with the Beckman AU5800 and its reagents were 48.4, 101.3, 96.6, 0.6, and 66.6 μmol/L. All five cases exhibited abnormal biochemical reaction curves. After treatment with normal saline, samples 1 and 5 yielded negative values, while after saturated saline treatment, sample 5 still showed a negative value and sample 1 showed an extremely low value, indicating incomplete correction of the interference. In contrast, the PEG precipitation method markedly improved the UA results, and the obtained values were comparable to those from the Abbott system.ConclusionThe PEG precipitation method provides superior correction compared to dilution with normal or saturated saline and yields results that are closer to the patient's true value.